2022
DOI: 10.3389/fpsyg.2022.953008
|View full text |Cite
|
Sign up to set email alerts
|

Toward an attentional turn in research on risky choice

Abstract: For a long time, the dominant approach to studying decision making under risk has been to use psychoeconomic functions to account for how behavior deviates from the normative prescriptions of expected value maximization. While this neo-Bernoullian tradition has advanced the field in various ways—such as identifying seminal phenomena of risky choice (e.g., Allais paradox, fourfold pattern)—it contains a major shortcoming: Psychoeconomic curves are mute with regard to the cognitive mechanisms underlying risky ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Here, by identifying a link between outcomes that are represented during choice evaluation and behavioral signatures that reflect consideration of either reward or probability information, we provide evidence that this variation is related to the types of information prioritized during evaluation. These results add to recent research demonstrating that heuristics and biases in choice can be explained for by individual differences in the types of information considered during the decision process 12 18 and demonstrate a link between these processes and previous research demonstrating the role of outcome reactivation in choice evaluation 21 , 22 , 24 26 , 44 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Here, by identifying a link between outcomes that are represented during choice evaluation and behavioral signatures that reflect consideration of either reward or probability information, we provide evidence that this variation is related to the types of information prioritized during evaluation. These results add to recent research demonstrating that heuristics and biases in choice can be explained for by individual differences in the types of information considered during the decision process 12 18 and demonstrate a link between these processes and previous research demonstrating the role of outcome reactivation in choice evaluation 21 , 22 , 24 26 , 44 .…”
Section: Discussionsupporting
confidence: 81%
“…Recent research has pointed to selective consideration of information as a source of bias in decision making. This work has analyzed eye-tracking, mouse-tracking, and response-times to reveal that selective consideration of choice options, attributes, or other information can explain biases in value-based consumer choice 12,13 , multi-attribute choice 14 , social choice 15 , intertemporal choice 16 , and risky decisionmaking [17][18][19] . Here, we expand on this work by first providing two additional forms of evidence, based on neural decoding and behavioral priming, for a relationship between selective consideration of information and heuristic strategy in decision-making under risk.…”
mentioning
confidence: 99%
“…We speculate that pauses may exert its effects by influencing predecisional attentional dynamics. Recent work has shown that attention allocation during risky decision can be systematically linked to the choices that people make (Zilker & Pachur, 2022). More concretely, more balanced attention between different attributes (e.g., probability versus outcome information) or between different options (e.g., the LP option versus HP option here) is associated with less distortion of relevant choice DECISION SPEED AND QUALITY 40 information (Pachur et al, 2018;Zilker & Pachur, 2021, which in turn may enable people to make choices that are more aligned with EV.…”
Section: How Do Pauses Increase Decision Quality In Risky Choices?mentioning
confidence: 99%